Anthelmintic resistance in cattle nematodes in northwestern São Paulo state, Brazil - Soutello, R. G. V.; Seno, M. C. Z.; Amarante, A. F. T. (Elsevier B.V., 2007)
The present study was carried out in the northwestern region of São Paulo State, Brazil, to determine the anthelmintic resistance status in cattle naturally infected with gastrointestinal nematodes. The anthelmintics tested were levamisole phosphate (Ripercol (R), Fort Dodge), albendazole sulphoxide (Ricobendazole, Fort Dodge), ivermectin (Ivomec (R), Merial) and moxidectin (Cydectin (R), Fort Dodge), administered at the doses recommended by the manufacturers. From April 2002 to May 2004, 25 cattle farms were evaluated. on each farm, steers were divided into treatment and control (not treated) groups based on fecal egg counts (FEC). Between 7 and 10 days after the anthelmintics administration, fecal samples were collected from each animal for post-treatment FEC. Fecal cultures from each group were also prepared for larval identification. After treatment, mean FEC reduction (FECR) in treatment groups (compared with control groups) was assessed on each farm. FECR was lower than 90% on 23 farms after ivermectin treatment. on 19 farms, FECR of 100% was recorded following moxidectin treatment; on the remaining 6, FECR ranged from 90% to 97.2%. After albendazole treatment, FECR was higher than 90% on 20 farms and ranged from 47.4% to 84.6% on other 5. After levamisole treatment, FECR was higher than 90% on 23 farms and equal to 47.4% and 73.7% on other 2 farms. Results indicated the presence of resistant Cooperia spp. and Haemonchus spp., especially to ivermectin; on some farms, resistance to albendazole and levamisole was also observed. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: anthelmintic resistance; ivermectin; cattle; Haemonchus; Cooperia